Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Kepuasan Kerja Pegawai Pada PT Pegadaian Cabang Manado Selatan - Chalvin Mario Manansang (Journal of Mandalika Literature, 2025)
This study aims to analyze the impact of Leadership and Organizational Culture on Employee Job Satisfaction at PT. Pegadaian Cabang Manado Selatan. The analytical method used in this research is multiple linear regression, with independent variables Leadership (X1) and Organizational Culture (X2), and the dependent variable Employee Job Satisfaction (Y). The analysis results show that the obtained multiple linear regression equation is ( Y = 0.484 + 0.056X1 + 0.748X2 + e ), where a constant of 0.484 indicates that when Leadership and Organizational Culture variables remain unchanged, the average Employee Job Satisfaction is 0.484. Based on significance tests, it is found that the Leadership variable (X1) has a significance value of 0.238, which is greater than 0.05, indicating that this variable does not have a significant partial effect on Employee Job Satisfaction. On the other hand, the Organizational Culture variable (X2) has a significance value of 0.000, which is less than 0.05, indicating that this variable has a significant effect on Employee Job Satisfaction. The F-test shows that the F- value of 56.955 is greater than the F-table value of 3.340, with a significance value of 0.000, which is less than 0.05. This indicates that, simultaneously, Leadership and Organizational Culture have a significant effect on Employee Job Satisfaction.